SOME ASPECTS OF SIMULATION-SEMANTIC MODEL OF PERFORMANCE INDICATORS SYNTHESIS IN THE ECONOMY - L. B. Shabanova; Y. P. Demidov; S. D. Vdovina (Russian Journal of Economics and Law)
Objective: to conduct a systematic analysis of the most frequent problems of the description and evaluation of a multidimensional state of socio-economic processes and to develop methodological recommendations on integrating a system of partial indices into a universal criterion. Methods: traditional methods of analysis, synthesis and information modelling. Results: the procedure is elaborated to integrate the system of private performance indicators, which ensures data comparability in the process of rating the different socio-economic processes and phenomena. Scientific novelty: using the methods of simulation-semantic modeling, as well as unique heuristic methods, the task is solved of assessing non-quantitative indicators and integrating them into a single evaluative criterion. Practical value: the approbation of methodical recommendations showed that their application allows to convert the multi-dimensional states of socio-economic processes into a single, one-dimensional evaluation criterion.